The Oxford handbook of religious diversity - Meister, Chad (Oxford University Press, 2011)
Introduction -- Part I: Contours of religious diversity -- Historical reflections on religious diversity / Martin E. Marty -- A religious studies approach to questions about religious diversity / Ian S. Markham -- A philosophical approach to questions about religious diversity / Peter Byrne -- A sociological approach to questions about religious diversity / Michele Dillon -- Part II: Key issues relevant to religious diversity -- Theological and philosophical issues -- Pluralism and relativism / Joseph Runzo -- Religious exclusivism / Paul K. Moser -- The diversity of religious experience / Keith E. Yandell -- Interreligious dialogue / Sallie B. King -- The religious alien / Paul J. Griffiths -- Religious diversity and a global ethic / Leonard J. Swidler -- Theology amidst religious diversity / Gavin D'Costa -- Religious diversity, theodicy, and the problem of evil / Michael L. Peterson -- Religion and revelation / Keith Ward -- Sociological and public policy issues -- Religious diversity and globalization / Peter Beyer -- Religious demographics and the new diversity / Frederick W. Norris -- New religious movements in global perspective / Peter B. Clarke -- Religion, race, and ethnicity / George Yancey -- Religious diversity, secularization, and postmodernity / John G. Stackhouse, Jr. -- Religion and multiple modernities / Christian Smith and Brandon Vaidyanathan -- Religious engagement and violence / Jessica Stern, Dalia Mogahed, and Tom Pyszczynski -- Religious diversity and public education / David Basinger -- Global religion and the environment / Roger S. Gottlieb -- Part III: Differing perspectives on religious diversity -- Multi-faith perspectives -- A Hindu perspective / Arvind Sharma -- A Buddhist perspective / Dabvid Burton -- An African religions perspective / Kwasi Wiredu -- A Chinese religions perspective / Chung-ying Cheng -- A Jewish perspective / David Shatz -- A Christian perspective / Charles Taliaferro -- An Islamic perspective / Majid Fakhry -- Gender and world perspectives -- A feminist perspective / Pamela Sue Anderson -- A continental perspective / Bruce Ellis Benson -- A naturalistic perspective / Michael Ruse